2017
DOI: 10.1101/213876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic conflict with a parasitic nematode disrupts the legume-rhizobia mutualism

Abstract: word count: 237 words 19 Total word count: 5095 words 20 Abstract 21Genetic variation for partner quality in mutualisms is an evolutionary paradox. One possible 22 resolution to this puzzle is that there is a tradeoff between partner quality and other fitness-23 related traits. Here, we tested whether a susceptibility to parasitism is one such tradeoff in the 24 mutualism between legumes and nitrogen-fixing bacteria (rhizobia). We performed two 25 greenhouse experiments with the legume Medicago truncatula. In … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 71 publications
2
52
0
Order By: Relevance
“…plant-pollinator, plant-seed disperser) mutualisms, as well as other plant-biotic interactions (e.g. herbivores, parasites) that vary in niche breadth and effects on host fitness (Segraves & Anneberg, 2016;Wood et al, 2018). Although previous studies have demonstrated that most organisms interact with multiple mutualistic partners, the benefits of generalization and underlying mechanisms remained largely unresolved (Douglas, 1998;Heath & Stinchcombe, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…plant-pollinator, plant-seed disperser) mutualisms, as well as other plant-biotic interactions (e.g. herbivores, parasites) that vary in niche breadth and effects on host fitness (Segraves & Anneberg, 2016;Wood et al, 2018). Although previous studies have demonstrated that most organisms interact with multiple mutualistic partners, the benefits of generalization and underlying mechanisms remained largely unresolved (Douglas, 1998;Heath & Stinchcombe, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of how fluctuating selective environments shape rhizobial, and other bacterial, populations will be advanced by incorporating greater ecological realism and microbiome complexity in experiments (e.g., Wood et al. ); by designing experiments to tease apart the separate effects of soil, rhizosphere, and nodule selection on rhizobial populations; by conducting experiments for longer than two host generations; and by expanding the genomic diversity of host genotypes. Such experiments would not only advance our understanding of how selection affects microbial populations, but also may inform efforts to leverage beneficial plant–microbe interactions to increase agricultural yields and aid in ecosystem restoration (Gopalakrishnan et al.…”
Section: Discussionmentioning
confidence: 99%
“…A general understanding of how strain fitness, plant fitness and N fixation change with climate and land-use changes will require comprehensive experiments spanning legume systems. Future research should examine how additional direct and indirect biotic players, such as phages (Hashem & Angle, 1990), other competing bacteria (Xiao et al, 2017), arbuscular mycorrhizal fungi (Ossler et al, 2015), nematodes (Wood et al, 2018) and herbivores (Paudel & Bede, 2015) modify interactions between rhizobia and legumes. Such a systems-level approach will allow functional characterization of the interactions of specific community members and advance understanding of the natural history of microbes (Busby et al, 2017;Martiny & Walters, 2018).…”
Section: Box 2 Applications For Agriculturementioning
confidence: 99%